Strength training in female distance runners: Impact on running economy - Johnston, R. E.; Quinn, T. J.; Kertzer, R.; Vroman, N. B. (The Journal of Strength and Conditioning Research, 1995)
Two groups of six trained female distance runners were evaluated on running economy, VO2max, and body composition. One group continued to train by running (4 days per week for a minimum of 20 miles) while the other ran similarly but also added three times per week sessions of upper and lower body heavy resistance training. Running economy improved in the strength group while in the other two indices there were no between group differences. The amount of running in these groups could be considered more in the classification of serious recreational runners rather than trained female distance runners as labeled by the authors. It is possible that the amount of running being performed did not tax the adaptive systems of Ss and the additional work contributed to greater levels of overall development. Implication. Both heavy resistance and distance running training improved running economy in serious female recreational runners when compared to a similar group performing running alone.